The Influence Of The Work Environment And Information Technology On The Performance Of Human Resources In The Pinrang Regency Course And Training Institute - Ibrahim Ibrahim; Rahmawati Umar; Rusdiah Hasanuddin; Tamsil Pattalolo; Haeruddin Haeruddin (Syntax Corporation, 2023)
This study aims to determine and analyze the effect of the work environment on the performance of Human Resources Skills and Training Institutes in Pinrang District, identify and analyze information technology on the performance of LKP human resources in Pinrang District, identify and analyze the effect of the work environment and information technology simultaneously on HR performance in Penang Regency. This research is a quantitative descriptive using a sampling technique with the Slovin method. Primary data from the results of the questionnaire as many as 48 samples were received and processed using SPSS 24 statistical tools using multiple linear regression methods. The research results obtained are the work environment has a positive but not significant effect on the performance of LKP Human Resources in Pinrang Regency, information technology has a positive and significant effect on HR performance in Pinrang Regency, the work environment and information technology simultaneously have a positive and significant effect on the performance of LPK HR in Penang Regency.